2003
DOI: 10.1300/j013v38n03_05
|View full text |Cite
|
Sign up to set email alerts
|

To Bleed or Not to Bleed: Young Women's Attitudes Toward Menstrual Suppression

Abstract: The purpose of this study was to investigate women's knowledge about and attitudes toward the medical suppression of menstruation. One hundred and three female undergraduate students completed several questionnaires. Thirty-five percent of the participants were familiar with menstrual suppression, and 12% reported using birth control methods to suppress their menses; oral contraceptive users were more knowledgeable about menstrual suppression than other women. Women who regarded menstruation as bothersome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 21 publications
1
54
1
Order By: Relevance
“…Many previous researchers have focused on specific perspectives of menstruation, like the experience of menarche (Fingerson, 2005;Lee, 2009;Orringer & Gahagan, 2010), menstrual education (Amaral, 2011;Beausang & Razor, 2000;Rembeck & Hermansson, 2008), menstrual symptoms (Johnston-Robledo et al, 2003;Santer et al, 2003;O'Flynn, 2006) or been based on beliefs about and attitudes towards menstruation (Marván, Ramírez-Esparza, Cortés-Iniestra & Chrisler, 2006). Our results, based on women's narratives, reveal the complexity surrounding menstruation as being an experience unique to each woman.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Many previous researchers have focused on specific perspectives of menstruation, like the experience of menarche (Fingerson, 2005;Lee, 2009;Orringer & Gahagan, 2010), menstrual education (Amaral, 2011;Beausang & Razor, 2000;Rembeck & Hermansson, 2008), menstrual symptoms (Johnston-Robledo et al, 2003;Santer et al, 2003;O'Flynn, 2006) or been based on beliefs about and attitudes towards menstruation (Marván, Ramírez-Esparza, Cortés-Iniestra & Chrisler, 2006). Our results, based on women's narratives, reveal the complexity surrounding menstruation as being an experience unique to each woman.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, there seems to be a correlation between severe menstrual pain, irregular menstrual cycles and heavy menstrual bleeding on the one hand and psychosocial stress on the other (Barnard, Frayne, Skinner & Sullivan, 2003;Yamamoto, 2009), which may result in a poorer health status (Barnard et al, 2003). Scholars indicate that women with a negative and bothersome experience of menstruation are more positive to menstrual suppression than women with more positive attitudes (Andrist, 2004;Johnston-Robledo, Ball, Lauta & Zekoll, 2003).…”
mentioning
confidence: 99%
“…She found that women who reported higher levels of self-objectification, the internalization of this view, were more likely to report negative attitudes toward and emotions regarding menstruation than women who reported lower levels of selfobjectification. Johnston-Robledo, Ball, Lauta, & Zekoll (2003) also found that women who scored higher on selfobjectification had more negative attitudes toward menstruation but not more positive attitudes toward menstrual suppression than women who scored lower on measures of self-objectification.…”
Section: Attitudes Toward Menstruationmentioning
confidence: 78%
“…They argued that self-objectification may represent a "flight" (p. 10) from this corporeality, which leads women to monitor or sanitize their bodies so that they conceal evidence of bodily functions, such as menstruation, that are viewed as disgusting and incompatible with physical attractiveness and sexual availability. Women who score higher on measures of selfobjectification have been found to report more negative attitudes toward menstruation (Johnston-Robledo, Ball, Lauta, & Zekoll, 2003;Roberts, 2004).…”
Section: Objectification Theorymentioning
confidence: 99%